Rancang Bangun Sistem Keamanan Motor Dengan Pengenalan Sidik Jari Berbasis Arduino Uno - Masnur, Masnur; Alam, Syahirun; Muhammad, Fikri Nasir (Jurnal Sintaks Logika, 2021)
Developments in science and technology is increasing , especially in the field of electronics , many benefits can be gained from the development of the electronics but the growing technology the more criminal offenses, including theft of a motor. Of this problem, made motorcycle security system through fingerprint recognition. The system is made using a fingerprint sensor Sm630 as input to detect fingerprints of motorcycle users. This system is also supported by the kit with Arduino uno ATmega328 microcontroller as the brain to process the data from the fingerprint sensor to the LCD, motorcycle and alarms. Of making this system, it can be concluded that, there will be only five users can access and motorcycle alarm system will turn on when there is no corresponding fingerprint sensor because the sensor attaches to will only communicate with fingerprint sensors are stored in the database .